Experimental research on the relationship between bypass diode configuration of photovoltaic module and hot spot generation *Project supported by the National Natural Science Foundation of China (No. 61504139, 61275040) and Chinese Academy of Sciences (No. Y072051002). (December 2018) - Gao, Cong; Liang, Peng; Ren, Huixue; Han, Peide
Abstract: A hot spot is a reliability problem in photovoltaic (PV) modules where a mismatched or shaded cell heats up significantly and degrades the PV module output power performance. High PV cell temperature due to a hot spot can damage the cell encapsulate and lead to second breakdown, which both cause permanent damage to the PV module. In present systems, bypass diodes are used to mitigate the hot spot problem. In this work, five commercial polysilicon PV modules configured with different numbers of bypass diodes are used to study the influence of bypass diodes on the reverse bias voltage of a shaded cell and the resulting hot spot phenomenon. The reverse bias voltage of the shaded cell, and the hot spot probability and severity decrease as the number of bypass diodes increases. Negative terminal voltage of a shaded cell accompanied by a switched-off bypass diode are the necessary condition for hot spot generation. In an extreme case where each cell has an individual bypass diode in a PV module, it still cannot avoid the hazards of a hot spot under the shading areas of 5–7 cm 2, but the probability of a hot spot is reduced to a minimum of 0.41%.